At‐Home Data Collection with an App‐Based Cognitive Assessment for Detecting Memory and Executive Functioning Changes in Aging and Pre‐Clinical AD. (20th December 2022) - Mechanic‐Hamilton, Dawn; Halberstadter, Kimberly; Lydon, Sean; Liebenberg, Erin; Wolk, David A.
Abstract: Background: Mobile, valid and engaging cognitive assessments are essential for detecting and tracking change in research participants and patients at risk for Alzheimer's Disease and Related Dementias (ADRDs). This pilot study aims to determine the feasibility of at‐home, app‐based memory and executive functioning tasks included in the mobile cognitive app performance platform (mCAPP), to detect cognitive changes associated with aging and preclinical AD. Method: The mCAPP includes three gamified tasks (Figure 1): (1) a "concentration" memory task that includes learning and matching hidden card pairs with increasing memory load, pattern separation features (lure vs. non‐lure), and spatial memory (2) a stroop‐like task ("brick drop") with speeded word and color identification and response inhibition components and (3) a digit‐symbol coding‐like task ("space imposters") with increasing pairs and incidental learning components. Participants also completed the NACC UDS3, additional paper and pencil tests, and NIH Toolbox measures. Participants used the mCAPP at home for two weeks. Participants included sixteen older adults (56% female; age=71.4±5.0, education=16.4±3.1; 63% White, 31% Black, 6% Multiracial) without cognitive impairment enrolled in the Penn ADRC cohort. Results: Participants played 12.1±4 times over two weeks, with 15/16 playing more than the assigned sessions. Almost all participants (88%) used a smartphone, but few (31%) played games on their phone. Usability rating was 6.2±0.7 (1‐7 scale) and most participants reported task difficulty was just right (75%‐81%). All tasks showed lower performance with increasing age and brick drop inhibition and space imposters also correlated with education (p's<0.05). Concentration performance correlated with UDS3 memory measures (p's<0.05, Figure 2). Brick drop performance correlated with measures of attention and executive functioning (p's<0.05, Figure 3). Space imposters correlated with the Digit Symbol Substitution Test (p<0.001, Figure 4). Some participants performed similarly across AM and PM sessions, while others showed differential performance. Initial change scores from the first to second session and from the 2 nd to the last sessions did not show significant change. Conclusion: This pilot study shows acceptability and usability of the app for at‐home use. Performance across measures indicate initial reliability and validity of mCAPP with continued data collection with a larger sample needed.